Pelatihan Bahasa Inggris Berekuivalensi Toefl Bagi Dosen Universitas Muhammadiyah Ponorogo - Lukman Syafii; Alip Sugianto (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2017)
Thisis training aims to help academicians of Muhammadiyah University of Ponorogo in effort to improve the mastery of English for lecturers, especially in the reparation of TOEFL (Test of English as a Foreign Language) with purpose to pursue Doctoral. Moreover, it is also directed to provive opportunity for lecturer to participate an integrated English Language training which is designed and oriented toward TOEFL mastery program with prescribed 450 minimum score. The activity lasted from 4th of August 2016 for more than two weeks. The required amount of time is related to time allocation provided by university in considering that this training is expected not to interfere university activities. The participants are as much as 15 lecturers from various faculties in University of Muhammadiyah Ponorogo.